Cp*Rh(iii)-catalyzed and solvent-controlled tunable [4 + 1]/[4 + 3] annulation for the divergent assembly of dihydrobenzo[cd]indoles and dihydronaphtho[1, 8-bc]azepines. Issue 12 (6th May 2022) - Zhang, Zhuo-Zhuo; Li, Ya; Shi, Bing-Feng
Abstract : A Cp*Rh-catalyzed solvent-switched tunable [4 + 1]/[4 + 3] cyclization of free 1-naphthylamines with propargyl carbonates is developed, providing dihydrobenzo[ cd ]indoles and dihydronaphtho[1, 8- bc ]azepines in moderate to good yields and broad range of functional groups. Abstract : Chemo- and regioselective Cp*Rh-catalyzed tunable [4 + 1]/[4 + 3] cyclization of free 1-naphthylamines with propargyl carbonates has been accomplished by regulating the reaction solvents. The reaction allowed a variety of dihydrobenzo[ cd ]indoles and dihydronaphtho[1, 8- bc ]azepines to be synthesized with broad functional group tolerance. In addition, mechanistic studies favored an intramolecular nucleophilic attack/protodemetalation/isomerization sequence or protonation/intramolecular nucleophilic substitution over β-O elimination/intramolecular cyclization.